Penggunaan Software Dan Hardware Terhadap Green Computing Perusahaan PCB Di Batam - Heri Nuryanto (Computer Based Information System Journal, 2014)
Progress and needs between software and hardware is always running in time, it is difficult to assess which one is superior. Both are two sides of the coin, on one side of the new software innovations require new hardware specification with technical specifications that can meet the requirements of the software, the most advanced hardware and vice versa can not be used if the software is not up to date. Instinctively and naturally as the user, have always wanted to try and have the latest software and hardware especially if they are need to support the smooth work. Green computing or the concept of environmentally friendly activities can be used as one form of manifestation of consciousness for people to care about the environment. This concept began to be introduced in 1992 by the U.S. Environmental Protection Agency (EPA). The purpose of this study was to obtain research results between penggaruh use software and hardware to green computing company Printed Circuit Board (PCB). Research object is located in Batam with a sample size of 100 companies using a multiple linear regression analysis. Based on the survey results and analysis, the percentage contribution of influence in getting the software and hardware to variable computing companies green PCB at 60.5%